2020
DOI: 10.1088/1755-1315/426/1/012012
|View full text |Cite
|
Sign up to set email alerts
|

The effect of crystalline material addition to concrete quality

Abstract: To improve the moisture susceptibility of concrete structure that will be exposed to water, an admixture should be added. One of the additives that can be added is Xypex C-1000 NF, which a crystalline material. A number of past studies have shown that this additive is effective in improving the moisture resistance of concrete structure. However, the application of this additive in Indonesia was found to be challenging as the performance of the concrete mixture was not as good as expected. This research aims to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 3 publications
0
6
0
Order By: Relevance
“…The findings obtained by Azarsa et al [26] indicated that 2% CA slightly increased the air content, and clearly reduced the slump in concretes regardless of the type of cement. In contrast, other result [54] noticed an increase in the slump values of concretes with CA. Innovative formulations promise to reduce the collateral effects of CAs in concretes when it comes to the negative impact on the workability, entrapped air and density [25].…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 71%
“…The findings obtained by Azarsa et al [26] indicated that 2% CA slightly increased the air content, and clearly reduced the slump in concretes regardless of the type of cement. In contrast, other result [54] noticed an increase in the slump values of concretes with CA. Innovative formulations promise to reduce the collateral effects of CAs in concretes when it comes to the negative impact on the workability, entrapped air and density [25].…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 71%
“…First, the investigations on the effect of CA as a permeabilityreducer on cementitious materials focus on the mechanical properties and durability. [14][15][16][17] Munn et al 15 reveal a considerable rise in compressive strength of concretes when 1.2% CA is added, and sulfate resistance as well as chloride resistance are also improved with the incorporation of CA. García-Vera et al 14 investigate the mechanical properties of mortar with CA in an aggressive environment, and results indicate that mortar with CA exhibits a greater compressive strength than the control one after a 90-day sulfuric acid exposure, but in short term this enhancement is less pronounced.…”
Section: Introductionmentioning
confidence: 99%
“…Robertson and Newtson 16 indicate that after a 10‐year laboratory and field monitoring study in marine environment, concrete mixtures with fly ash or silica fume show a superior corrosion‐inhibiting performance compared with the concrete mixtures with CAs. Nataadmadja et al 17 find that the incorporation of CA enhances the compressive strength of normal strength concrete. Second, as a self‐healing stimulator, CA is always introduced in cementitious materials for crack healing 18–20 .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations